Analisis Emosi Anjing Melalui Klasifikasi Citra untuk Deteksi Ekspresi Wajah Hewan Peliharaan - I Gede Surya Adi Pradana; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Emotion Detection in Dogs through Image Classification for Pet Facial Expression Analysis utilizes convolutional neural networks (CNNs) to discern and quantify dogs' emotional states based on their facial expressions. This approach leverages advanced image processing techniques to recognize subtle cues indicative of various emotions like happiness, fear, or sadness in dogs. By applying CNNs to analyze image data, pet owners can gain valuable insights into their dogs' emotional well-being and address their needs accordingly. This technology offers a promising avenue for enhancing the bond between pets and owners by facilitating more informed and empathetic care tailored to each dog's emotional state and personality.